Mr. Mehtas dilemma : a case of performance appraisal politics - Chandwani, Rajesh, (SAGE Knowledge. Cases., 2017)
Mr. Jeevan Mehta, the Regional Head HR, was rather unsure about the decision he had made. While Mr. Mehta thought he had worked out the best possible solution to Mr. Rajesh Kumars dilemma, he was not certain if it would pan out the way he expected it to. But then, the nature of the problem was also queer: the kind he had never had to deal with before. Mr. Mehtas decision had the backing of not just Mr. Yogesh Desai, Rajeshs reporting manager and performance appraiser, but also his department head. Yet, there seemed to be an air of doubt about the whole issue.